Global pattern of cardiovascular disease management in patients with cancer and impact of COVID-19 on drug selection: IRAQ—IC-OS survey-based study - Farhan, Hasan Ali; Yaseen, Israa Fadhil; Alomar, Mohammed; Lenihan, Daniel; Dent, Susan; Lyon, Alexander R. (Frontiers in Cardiovascular Medicine, 2022)
Background: Regional variations in cardiovascular disease (CVD) and CVD management are well known. However, there is limited information on geographical variations in the discipline of Cardio-Oncology, including both the nature of CVD in patients with cancer and the management. Furthermore, during the recent COVID-19 pandemic, CV care for patients was disrupted resulting in an unknown impact on cardio-oncology services. Objectives: To identify the regional variations in the management of CVD among patients with cancer and the impact of COVID-19 pandemic on the selection of cardiovascular drugs in cardio-oncology. Methods: An online survey was conducted by the Iraq Chapter of the International Cardio-Oncology Society (IC-OS). The survey was shared with cardiologists and oncologists in all seven continents to identify whether regional variations exist in cardio-oncology daily practice. Results: From April to July 2021, 140 participants responded to the survey, (72.9%) cardiologists and (27.1%) oncologists. Most of the respondents were from the Middle East (26.5%), North America (25%), Latin America and the Caribbean, and Europe (25%). Baseline CV risk assessment in cancer patients using the HFA/IC-OS score was reported in (75.7%) of respondents [(78.4%) cardiologists and (68.4%) oncologists]. Hypertension was the most common CVD treated by the survey respondents globally (52.1%) unlike in Europe where heart failure was the most prominent CVD (51.7%). Blood pressure cutoff value to initiate hypertension management is >140/90 mmHg globally (72.9%), but in North America (48.6%) it was >130/80. In the Middle East 43.2% of respondents do not use cardioprotective medication. During COVID-19 pandemic (10.7%) of respondents changed their practice, such as switching from prescribing ACEI to ARB. Apixaban is the main anticoagulant used in patients with cancer (32.9%), however, in cancer patients with COVID-19 infection the majority used enoxaparin (31.4%). Conclusion: More than three quarter of cardiologists and oncologists responding to the survey are using HFA/IC-OS proformas. Survey showed regional variations in the management of CVD at different continents. Use of cardioprotective agents was limited in some regions including the Middle East. COVID-19 pandemic impacted daily practice on the selection and switching of cardiovascular drugs including ACEI/ARB and the choice of anticoagulant.